Intratumoural production of TNFα by bacteria mediates cancer therapy - Murphy, Carola (PLoS One, 2017)
Systemic administration of the highly potent anticancer therapeutic, tumour necrosis factor alpha (TNFα) induces high levels of toxicity and is responsible for serious side effects. Consequently, tumour targeting is required in order to confine this toxicity within the locality of the tumour. Bacteria have a natural capacity to grow within tumours and deliver therapeutic molecules in a controlled fashion. The non-pathogenic E. coli strain MG1655 was investigated as a tumour targeting system in order to produce TNFα specifically within murine tumours. In vivo bioluminescence imaging studies and ex vivo immunofluorescence analysis demonstrated rapid targeting dynamics and prolonged survival, replication and spread of this bacterial platform within tumours. An engineered TNFα producing construct deployed in mouse models via either intra-tumoural (i.t.) or intravenous (i.v.) administration facilitated robust TNFα production, as evidenced by ELISA of tumour extracts. Tumour growth was impeded in three subcutaneous murine tumour models (CT26 colon, RENCA renal, and TRAMP prostate) as evidenced by tumour volume and survival analyses. A pattern of pro-inflammatory cytokine induction was observed in tumours of treated mice vs. controls. Mice remained healthy throughout experiments. This study indicates the therapeutic efficacy and safety of TNFα expressing bacteria in vivo, highlighting the potential of non-pathogenic bacteria as a platform for restricting the activity of highly potent cancer agents to tumours.